1980
DOI: 10.1021/bi00553a003
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phosphatidylglycerol asymmetry in small, unilamellar vesicles by chemical modification

Abstract: We report the adaptation of a simple, precise chemical assay for vicinal hydroxyl groups to the determination of phosphatidylglycerol transbilayer distribution in small, unilamellar vesicles. Conditions are described under which the chemical procedure reveals only phosphatidylglycerol molecules exposed on the surface of intact phospholipid vesicles. Other assay conditions reveal all the phosphatidylglycerol in the vesicle. Vesicle size distributions have been determined by gel permeation chromatography. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
43
1

Year Published

1984
1984
2004
2004

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 25 publications
(42 reference statements)
6
43
1
Order By: Relevance
“…What is remarkable about the transmembrane distribution of GalCer is its strong preference for the inner leaflet when present at 1 or 2 mol % in POPC SUVs. Earlier studies of PE and PG (see Introduction) revealed just the opposite behavior in that these lipids strongly preferred the outer leaflet of PC SUVs (29,30). Only when present at 10 mol % (or more) in PC SUVs did PE and PG assume transmembrane distributions that can be rationalized by the structural parameters associated with their overall shape, charge, and hydration (22,29,30).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…What is remarkable about the transmembrane distribution of GalCer is its strong preference for the inner leaflet when present at 1 or 2 mol % in POPC SUVs. Earlier studies of PE and PG (see Introduction) revealed just the opposite behavior in that these lipids strongly preferred the outer leaflet of PC SUVs (29,30). Only when present at 10 mol % (or more) in PC SUVs did PE and PG assume transmembrane distributions that can be rationalized by the structural parameters associated with their overall shape, charge, and hydration (22,29,30).…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies of PE and PG (see Introduction) revealed just the opposite behavior in that these lipids strongly preferred the outer leaflet of PC SUVs (29,30). Only when present at 10 mol % (or more) in PC SUVs did PE and PG assume transmembrane distributions that can be rationalized by the structural parameters associated with their overall shape, charge, and hydration (22,29,30). The preferential localization of low mole fractions of PE and PG to the outer leaflet of PC SUVs has been explained as a general lattice response linked to the "looser" molecular packing of the outer leaflet of PC SUVs (30).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Yet, in addition to the salt concentration and pH in solution, the composition of mixed lipids ought to affect the distribution of a component lipid in the vesicle. There have been reports presenting different views on the asymmetry of certain phospholipids in the vesicle [14,15,18,19]. However, the methods used might have led to different conclusions.…”
Section: Discussionmentioning
confidence: 99%